Unconscious Human Behavior at Visceral Level of Emotional Design - Muhammad Jameel, Mohamed Kamil; Shahriman, Zainal Abidin (Elsevier Science, Ltd., 2013)
In the near future, the emphasis on product design innovation will be on finding a fit between technology and human values. However, there is still a limited discussion available on the unconscious human behaviour as well as inadequate literature related to the visceral level of emotional design. The purpose of this study is to manipulate the value of view of multidisciplinary experts. The paper's goal is to provide a new perimeter of design thinking with respect to the emotional design, as well as the direction for the development of innovative product design.